2017
DOI: 10.1111/sms.13015
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of exertional fatigue in the heat: A review of magnetic resonance imaging methods

Abstract: The central nervous system, specifically the brain, is implicated in the development of exertional fatigue under a hot environment. Diverse neuroimaging techniques have been used to visualize the brain activity during or after exercise. Notably, the use of magnetic resonance imaging (MRI) has become prevalent due to its excellent spatial resolution and versatility. This review evaluates the significance and limitations of various brain MRI techniques in exercise studies-brain volumetric analysis, functional MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…It has been revealed that central nervous system plays a role in the development of fatigue in repeated high-intensity exercise [9]. Several studies using functional magnetic resonance imaging have found increased activations in sensory processing and motor-related brain regions such as primary motor cortex, supplementary motor area and pre-motor cortex while performing fatiguing exercise tasks [30]. These activations suggest a greater perception of effort under fatigue and the need for higher motor output to sustain the same physical workload [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that central nervous system plays a role in the development of fatigue in repeated high-intensity exercise [9]. Several studies using functional magnetic resonance imaging have found increased activations in sensory processing and motor-related brain regions such as primary motor cortex, supplementary motor area and pre-motor cortex while performing fatiguing exercise tasks [30]. These activations suggest a greater perception of effort under fatigue and the need for higher motor output to sustain the same physical workload [31].…”
Section: Discussionmentioning
confidence: 99%
“…The local connectivity of functional brain networks decreases in hyperthermia, which can lead to cognitive impairment (Tan et al, 2018). However, studies have obtained mixed results regarding the effect of hyperthermia in go/no-go tasks, reporting that reaction times and error rates worsened (Ando et al, 2015) or were unaffected (Shibasaki et al, 2019) after strenuous exercise in a hot environment.…”
Section: Discussionmentioning
confidence: 99%
“…Following discussions with sports experts and athletes, we combined a literature review and analysis of fatigue-related studies ( Carroll et al, 2017 ; Tan et al, 2018 ; Ratka et al, 2020 ) to determine the main research subject of the 2 types of fatigue. Comprehensively considering previous fatigue-related scales and the physiological characteristics of AEF, 14 questions were initially screened.…”
Section: Methodsmentioning
confidence: 99%
“…Fatigue originations can be classified as either peripheral or central ( Meeusen, 2014 ; Carroll et al, 2017 ; Tan et al, 2018 ; Ratka et al, 2020 ). Dysfunction of muscle contraction during exercise can induce peripheral fatigue ( O’Leary et al, 2016 ), mainly caused by consumption of energy materials, accumulation of metabolites, and material imbalance in the body ( Chang and Zhang, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation